ASSOCIATION BETWEEN ANTIHYPERTENSIVE AND LIPID-LOWERING THERAPY, BONE MASS, AND OSTEOPOROSIS RISK FACTORS - K. E. Sobchenko; I. A. Skripnikova; V. E. Novikov; T. V. Popkova; I. S. Dydykina; A. V. Smirnov; V. A. Vygodin; E. L. Nasonov; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To evaluate the association between β-adrenoblocker (β-AB), angiotensin-converting enzyme inhibitor (ACEI), and statin therapy, bone mineral density (BMD), and osteoporosis risk factors (RFs).Material and methods. This retrospective study (n=1163) included 42 men and 1121 women aged >40 years, who underwent densitometry before the start of the osteoporosis therapy. The main group (MG) included 418 people receiving β-AB, ACEI, statins, or their combination for at least 6 months before densitometry. The control group (CG) included 745 untreated patients. The data on RFs and pharmacological therapy came from ambulatory case histories and telephone surveys. BMD was measured by X-ray densitometry of lumbar spine and femur.Results. In patients who received antihypertensive (AHT) and lipid-lowering therapy (LLT), the risk of bone mass (BM) reduction was lower than that in CG (odds ratio (OR) 1,6; 95% confidence interval 1,25–2,022; p<0,001); the osteoporosis incidence was 1,3 times lower; and all BMD measurements were significantly higher than in untreated patients. The highest BMD was observed in patients on combined therapy which included statins. The odds of BM reduction by such factors as age, postmenopause duration, early and surgical menopause, low body mass, low physical activity (LPA), previous fractures, fractures in relatives, rheumatoid arthritis, glucocorticoid therapy, and alcohol abuse, were similar in MG and CG. In logistic regression analyses, these factors were not associated with the protective effects of the medications on BMD. The number of peripheral fractures was higher in MG than in CG (36% vs. 26%). This was due to the fact that in the MG, patients were older (mean age 62,5±8,52 years, vs. 57,8±8,2 years in CG), more likely to report LPA (>50%), and potentially, more prone to adverse effects of AHT which could result in more frequent falls.Conclusion. Treatment with β-AB, ACEI, and statins is associated with higher BMD of both lumbar spine and proximal femur. With the exception of age and postmenopause duration, osteoporosis RFs did not influence the effects of cardiovascular treatment.